The methylating agent streptozotocin induces persistent telomere dysfunction in mammalian cells - Paviolo, Natalia Soledad (2015)
We analyzed chromosomal aberrations involving telomeres in the progeny of mammalian cells exposed to the methylating agent and antineoplastic/diabetogenic drug streptozotocin (STZ), to test whether it induces long-term telomere instability (by chromosome end loss and/or telomere dysfunction). Rat cells (ADIPO-P2 cell line, derived from Sprague-Dawley rat adipose cells) were treated with a single concentration of STZ (2mM). Chromosomal aberrations were analyzed 18h, 10 days, and 15 days after treatment, using PNA-FISH with a pan-telomeric probe [Cy3-(CCCTAA)3] to detect (TTAGGG)n repeats. Cytogenetic analysis revealed a higher frequency of chromosomal aberrations in STZ-exposed cultures vs. untreated cultures at each time point analyzed. The yield of induced aberrations was very similar at each time point. Induction of aberrations not involving telomere dysfunction was only observed 18h and 15 days after treatment, whereas induction of telomere dysfunction-related aberrations by STZ (mainly in the form of telomere FISH signal loss and duplications, most of them chromatid-type aberrations) was observed at each time point. Our results show that STZ induces persistent telomere instability in mammalian cells, cytogenetically manifested as telomere dysfunction-related chromosomal aberrations. Neither telomere length nor telomerase activity is related to the telomere dysfunction.